Approaches to the study of the environment and mining exploitation in the extreme south of Peru. XVI - XVIII centuries - Yábar, Ben Yusef (2020)
This paper makes an initial review of the environment and the mining exploitation carried out in the south-Peruvian extreme between the 16th and 18th centuries in an effort to approach qualitatively inferring some impact of mining exploitation on the environment. With the sources reviewed, it is a high probability that mining exploitation would have an unfavorable impact on the environment, mainly in the human or demographic component, due to the evident demographic decline, and that it could be due to mining exploitation, the mining mita, and enganche; All these activities carried out in the territories studied. The initial inference should be contrasted with the study of primary sources to have a greater certainty of the inferred and of the other dimensions of the environment as a study variable.